Case Study on Profit-Maximizing Combination of Vegetable Crops for Small-Scale Farmers in Leyte, Philippines - Wendy C. Enerlan; Ma. Salome B. Bulayog (Review of Socio-Economic Research and Development Studies, 2020)
Intercropping is one of the potential agricultural practices that can help maximize productivity given limited farm area. This study seeks to compare the production output from the existing vegetable combinations grown under intercropping, which could be useful to farmers in the Visayas, particularly in Leyte. Gross margin analysis was conducted to evaluate the profitability of each crop mix. A linear programming model was used to determine optimal land use options for the identified vegetable mixes. Results show that farmers can increase profit across different crop combinations using linear programming approach. In particular, the gross margin analysis results show that sweet pepper-eggplant intercropping combinations provide farmers the highest profit per m2. This combination could maximize profit up to PHP211,887 per 608.97m2 of farm area, as suggested from the linear programming analysis. Farmers can achieve maximum profit using the optimal mix of crops, allocating about 551.28m2 for eggplant production while allocating 57.69m2 in producing sweet pepper. This study suggests that the choice of small-scale vegetable farmers in intercropping could be enhanced by utilizing linear programming approach. Through linear programming, profit can be maximized, and this approach should be coupled with technical assistance on horticultural aspects and capacity-building activities for farmers.